The Role of Religious Education in Shaping the Character of the Younger Generation - Joshua Christian Wenas; Kezia Verana (International Journal of Christian Education and Philosophical Inquiry, 2024)
The purpose of this study is to investigate how religious education influences the development of a person's character in their early adult years. A person's identity, moral independence, and life values are formed during the crucial developmental stage of early adulthood, which has a big influence on their future. This study examines the role that Christian Religious Education plays in promoting character development that embodies Christian values like love, honesty, responsibility, and integrity using a qualitative research approach based on a literature review. According to the findings, Christian Religious Education is crucial for raising people's moral consciousness, establishing spiritual principles, and assisting them in overcoming social obstacles. Christian Religious Education helps people develop a Christ-centered identity, improves their capacity for responsible decision-making, and promotes engagement in worthwhile social activities by teaching them God's Word. This study does, however, also point out a number of issues that could compromise the efficacy of character education, including the impact of digital media and social settings. According to the study's findings, Christian religious education plays a vital role in forming morally pure and motivated young adults. To foster an atmosphere that encourages character development, families, educational institutions, and society must work together. It is anticipated that the results will offer useful insights for creating more pertinent and successful Christian Religious Education initiatives.